O potrzebie czytania niemieckich filozofów. Witkacy o Boyu Witkacy on Boy - Panek, Sylwia (Przestrzenie Teorii, 2025)
The article discusses Witkacy’s attitude towards the amicable reviewer of his plays–Tadeusz Boy Żeleński. Witkacy’s criticism of Boy, the esteemed author of Flirt z Melpomeną (Flirt with Melpomene), is primarily based on his literary credo. Witkacy demanded that when evaluating art, a strictly aesthetic perspective should be adopted, thereby not accepting Boy Żeleński’s conviction that social passions should dominate in thinking about literature. Moreover, Witkacy did not recognise the former’s acceptance that the critic be a moderator of social life. His attack on Boy-Żeleński resulted from the belief that the shortcoming of the reviewer’s attitude was his resignation from embedding reflections on literature and theatre in metaphysics and the aesthetic concept rooted therein.